Design and Development of Onion Storage Shade for Better Ventilation and Longer Life - O.D. Hulekar; S.R. Gadhe; A.B. Gade; S.A. Gite; S.A. Bawake; V.P. Bhaurkar; L.S. Dhamande (International Journal of Trends in Horticulture, 2026)
Onions are one of the most important cash crops for farmers in India and many other countries. However, most harvested onions are lost every year due to improper storage. Traditional storage methods, such as keeping onions in heaps under trees, in closed rooms, or in poorly ventilated sheds, do not provide sufficient airflow. As a result, moisture accumulates, leading to sprouting, fungal growth, rotting, and physical damage. These losses reduce farmers’ income and create instability in market prices. To solve this problem, an improved onion storage shade has been designed with a focus on natural ventilation and cost-effectiveness. The structure is raised above ground level on a platform to prevent moisture from entering from the soil. This elevation also allows air to circulate from below. The side walls are made with perforated materials, such as bamboo slats, wooden battens, or wire mesh, which ensure continuous cross-ventilation. Proper airflow is essential because onions release moisture during storage, and removing this moisture helps maintain their quality. The roof is designed in a ridge shape, allowing hot air to rise and escape through the top. This reduces internal temperature and prevents condensation. The roofing material can be locally available sheets, tiles, or thatch, depending on regional climate conditions. The structure is simple, durable, and affordable, making it easy for small and medium farmers to adopt without heavy investment. Early field trials have shown a significant reduction in storage losses compared to traditional methods. By keeping onions dry, cool, and well-ventilated, the improved shade maintains firmness, reduces sprouting, and preserves weight. This allows farmers to store onions for longer periods and sell them when market prices are favorable. Overall, this improved storage shade supports better income stability, reduces post-harvest waste, strengthens the supply chain, and contributes to food security. It is a practical and sustainable solution that empowers farmers and promotes agricultural development.
Keywords: Agricultural engineering; Storage shade; natural airflow; onion storage; post-harvest losses; shelf life; ventilation